Investigation of the sense of school belonging and sportspersonship behavior of students playing traditional children’s games - Ahmet Temel; Hüdaverdi Mamak; Murat Kangalgil; İbrahim Kılıçer; Cesur Erdem; Tuba Çapar; Abdulgani Özkan; Süleyman Uz (BMC Psychology)
Abstract The purpose of this study is to examine the sense of school belonging and sportspersonship behaviors of students who participate in traditional children's games. The research was designed using a quasi-experimental model with a pre-test and post-test control group and was conducted over a period of 16 weeks. The study group consisted of a total of 1871 students, including 1379 middle school and 492 high school students, continuing their education in Eskil, Aksaray during the 2023–2024 academic year. The experimental group students participated in the games and inter-school tournaments within the scope of the “2nd I Live My Values with Traditional Games Project” No intervention was applied to the control group after the introduction of the games. The “School Belongingness Scale” and the “Physical Education Course Sportspersonship Behavior Scale” were used as data collection tools. For data analysis, MANOVA, paired samples t-test, and regression analysis were employed. The findings of the study indicated that both the experimental and control groups showed positive scores in pre-test and post-test measures of school belongingness and sportspersonship behaviors. However, the experimental group demonstrated significant improvements in their sense of school belonging and sportspersonship behaviors in favor of the post-test. While no significant change was observed in the control group's sense of school belonging, a decline was noted in their sportspersonship behaviors. The experimental group exhibited greater development in school belongingness and sportspersonship behaviors compared to the control group. Although middle school students showed improvements in their sense of school belonging, high school students experienced a more substantial emotional development. No significant differences were found in school belongingness and sportspersonship behaviors based on the students' gender. Sportspersonship behavior predicted school belongingness by 11%, suggesting that positive sportspersonship behaviors increased school attachment among children. In conclusion, it was determined that students participating in traditional children's games developed a more positive sense of school belonging and sportspersonship behaviors over time. Based on the positive outcomes of student participation in traditional games, it is recommended to promote these games, incorporate them into physical education classes, and increase participation in tournaments.